Modeling Dynamic Patients Variables to Renal Failure in the Intensive Care Unit Using Bayesian Networks - Shah N.N.H. (Institute of Electrical and Electronics Engineers Inc., 2023)
Bayesian networks; Blood pressure; Classification (of information); Creatinine; Failure (mechanical); Machine learning; Bayesia n networks; Comorbidities; Data discretization; Failure assessment; Machine-learning; Model dynamics; Organ failure; Renal failure; Sequential organ failure assessment score; Variables selections; Intensive care units